2015
DOI: 10.4103/2394-5079.168078
|View full text |Cite
|
Sign up to set email alerts
|

Dietary incorporation of jojoba extract eliminates oxidative damage in livers of rats fed fumonisin-contaminated diet

Abstract: International audienceAim: This study aimed to determine the composition of ethanol extract of jojoba seeds, and to evaluate its hepatoprotective effects in rats fed fumonisin B1 (FB1)-contaminated diet.Methods: Jojoba seeds were extracted in 95% ethanol, and the chemical composition was determined. Male rats were divided into six groups and treated for 8 weeks as follows: (1) Untreated control; (2) FB1-contaminated diet (80 mg/kg diet); (3) low dose (0.5 mg/kg b.w.) jojoba extract; (4) high dose (1.0 mg/kg b.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
3
5
0
Order By: Relevance
“…Similarly, groups G11, G12, and G13 showed a significant reduction in serum levels of creatinine, urea, cholesterol, and triglyceride comparing with high AFS control (G4). These observations are agreed by that of Ayoub et al, (2011);Abdel-Wahhab, et al, (2016) and Sobhy, et al, (2016) that used Jojoba oil and Nigella cake protein as feed supplement. Urea is formed in the liver and represents the principal end product of protein catabolism.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, groups G11, G12, and G13 showed a significant reduction in serum levels of creatinine, urea, cholesterol, and triglyceride comparing with high AFS control (G4). These observations are agreed by that of Ayoub et al, (2011);Abdel-Wahhab, et al, (2016) and Sobhy, et al, (2016) that used Jojoba oil and Nigella cake protein as feed supplement. Urea is formed in the liver and represents the principal end product of protein catabolism.…”
Section: Resultssupporting
confidence: 92%
“…The increase of ALT level by HFHF diet was reversed by ND and jojoba meal while staying on a diet without high-fat high-fructose or on diet mixed with HFHF diet. Our results were in agreement with Abdel-Wahhab et al [43]. These authors showed a decrease in the ALT level by ethanolic extract.…”
Section: Discussionsupporting
confidence: 94%
“…Feeding curcumin to afla-intoxicated mice resulted in significant improvement in levels of TAC and SOD. Our results were in accordance to those of Choi et al, (2011) and Abdel-Wahhab et al (2016). It was clear from the results that AFs have adverse effects on mice health via their ability to induce oxidative stress that furthermore led to the promotion of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%